1973
DOI: 10.1139/v73-585
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Sulfite Ion with 2,4,6-Trinitrobenzaldehyde: Kinetic, Equilibrium, and Proton Magnetic Resonance Studies

Abstract: Sulfite ion reacts with 2,4,6-trinitrobenzaldehyde in aqueous solution of ionic strength 0.14 M to yield a 1 :1 o-con~plex at low sulfite concentrations and a 2: 1 o-complex at high sulfite concentrations. The visible absorption characteristics of these two o-complexes as well as equilibrium constants and relevant thermodynamic parameters for their formation have been determined. P.n~.r. studies demonstrate that two isomeric forms of the 1 : 1 o-complex occur in aqueous dimethylsulfoxide solution and two isome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…According to the standard reduction potentials of relevant sulfur redox couples (e.g., HS – , S n 2– , SO 3 2– , and S 2 O 3 2– ; see Table S5, Supporting Information), it appears that SO 3 2– and S 2 O 3 2– are thermodynamically capable of reducing dinitroanilines. Previous studies, however, have shown that SO 3 2– and S 2 O 3 2– may only act as nucleophiles and undergo rapid reversible formation of anionic Meisenheimer complexes with NACs including dinitroanilines. Such reversible reactions, however, did not seem to compete with the reductive transformation promoted by HS – and S n 2– .…”
Section: Resultsmentioning
confidence: 95%
“…According to the standard reduction potentials of relevant sulfur redox couples (e.g., HS – , S n 2– , SO 3 2– , and S 2 O 3 2– ; see Table S5, Supporting Information), it appears that SO 3 2– and S 2 O 3 2– are thermodynamically capable of reducing dinitroanilines. Previous studies, however, have shown that SO 3 2– and S 2 O 3 2– may only act as nucleophiles and undergo rapid reversible formation of anionic Meisenheimer complexes with NACs including dinitroanilines. Such reversible reactions, however, did not seem to compete with the reductive transformation promoted by HS – and S n 2– .…”
Section: Resultsmentioning
confidence: 95%
“…[3][4][5][6][7][8] Reports of attack at substituted ring positions leading to nucleophilic displacement are relatively scarce, although it is known that substitution of halide ions leads to the formation of derivatives of benzene sulphonic acid, 9,10 and there is one early report of the formation of an adduct by attack at the 1-position of 2,4,6-trinitrobenzaldehyde. 11 Here we compare the reactions with sulphite of the ethyl and phenyl ethers of 2,4,6-trinitrophenol and 2,4,6-trinitrothiophenol. It is known 12,13 that phenoxide and thiophenoxide are considerably better leaving groups than their aliphatic analogues, ethoxide and thioethoxide respectively.…”
Section: Introductionmentioning
confidence: 99%